2022
DOI: 10.21203/rs.3.rs-1239550/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Folic Acid Conjugated Silver Nanoparticles in Treatment of RA like Adjuvant Arthritis in Rats.

Abstract: Objective: Nanomedicine has become one of the promising research areas, opening new horizons in disease diagnosis and treatment. Recent years have witnessed a surge in the development of nanomedicine for combating rheumatoid arthritis (RA), the most common autoimmune arthritis. RA is characterized by progressive inflammation and persistent synovitis, leading to joint destruction, functional incapability, and ultimately disability. Although there has been a tremendous evolution in disease assess­ment and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results of this study contradict those obtained (Nigatu et al 2017) (Al-Naseem et al 2021 (Islam, Islam, and Sultana 2020) (Corrado et al 2017) . These studies confirmed a decrease in the total number of red blood cells in patients with In rheumatoid arthritis, approximately 17% of RA patients were found to have low hemoglobin levels and met WHO criteria (Hajar 2015) Cell migration is important in innate and adaptive immune responses and leukocyte recruitment to sites of acute or chronic inflammation (Lin et al 2015) Inadequate leukocyte assembly reduces inflammatory responses and initiates pathological processes of inflammation (Poulet et al 2010) Leukocytes sharply increase as the body's first line of defense (Kebede et al 2016) Concentration of white blood cells and lymphocytes possibly triggering a mechanism Immune defense (Nafiu et al 2020) Increasing the number of white blood cells by stimulation during the rise of inflammatory cytokines (G. Chen et al 2020) and when using MTX treatment, we notice a decrease in the values of (RBC, MCV, MCHC, MCH) and this corresponds to With a study (Elbeialy 2022) (De Rotte et al 2018 approximately 60% of the drugs used are of natural origin at present (Albert et al 2021) , RA patients who are likely to be unresponsive to MTX therapy, may treat ( Additionally) with other biologics or medicines (De Rotte et al 2018) plants can be used to treat a myriad of diseases (Saganuwan 2017) . A natural flavonoid, widely present in many plants (X.…”
Section: Resultsmentioning
confidence: 60%
“…The results of this study contradict those obtained (Nigatu et al 2017) (Al-Naseem et al 2021 (Islam, Islam, and Sultana 2020) (Corrado et al 2017) . These studies confirmed a decrease in the total number of red blood cells in patients with In rheumatoid arthritis, approximately 17% of RA patients were found to have low hemoglobin levels and met WHO criteria (Hajar 2015) Cell migration is important in innate and adaptive immune responses and leukocyte recruitment to sites of acute or chronic inflammation (Lin et al 2015) Inadequate leukocyte assembly reduces inflammatory responses and initiates pathological processes of inflammation (Poulet et al 2010) Leukocytes sharply increase as the body's first line of defense (Kebede et al 2016) Concentration of white blood cells and lymphocytes possibly triggering a mechanism Immune defense (Nafiu et al 2020) Increasing the number of white blood cells by stimulation during the rise of inflammatory cytokines (G. Chen et al 2020) and when using MTX treatment, we notice a decrease in the values of (RBC, MCV, MCHC, MCH) and this corresponds to With a study (Elbeialy 2022) (De Rotte et al 2018 approximately 60% of the drugs used are of natural origin at present (Albert et al 2021) , RA patients who are likely to be unresponsive to MTX therapy, may treat ( Additionally) with other biologics or medicines (De Rotte et al 2018) plants can be used to treat a myriad of diseases (Saganuwan 2017) . A natural flavonoid, widely present in many plants (X.…”
Section: Resultsmentioning
confidence: 60%